Implementasi Peraturan Bupati Tabanan Nomor 24 Tahun 2018 Tentang Action Plan Tourism Modelsdi Desa Belimbing - Sumitra Jaya, I Gede; Dwi Wismayanti, Kadek Wiwin; Yudharta, Putu Dharmanu (CITIZEN CHARTER; Vol 1 No 2 (2019), 2020)
ABSTRACT Regulation the Regent of Tabanan Number 24 on 2018 th concerning the Action Plan Tourism Models for developing a tourist village in the Nikosake area. This policy aims to create new economic generator and develop existing potential in western Tabanan especially in Belimbing Village. This study has purpose is tokfindkoutjhow thee development of Belimbing Tourism Village based on the Action Models of Tourism Models so as to provide social and economic change for the community. This study based on Van Meters and Van Horn theory about Policy Implementation and the results of this policy research in Belimbing Village have achieved good results in several indicators such as standards and targets, characteristics of organizations, organizations communication, and condition of social, economic, and political, but not maximal on resource indicators, characteristics of implementing organizations, and their attitudes. These deficiencies occur in large part due to problems in human resources and financial resources.   Keywords: Implementation, Regional Development, Tourism Village, Nikosake